Transformation Work Discipline, Leadership Style, And Employees Perfomance Based 21st Century Global Citizens Limited Company - Muhtadin, Imam; Yusuf, Muhammad; Ramadhan, Farras; Wahdana, Hudan (Universitas Muhammadiyah Jakarta, 2023)
To compete and flourish in accomplishing company goals in the Industrial Revolution 4.0, a more sophisticated and fast-developing world, organizations must increase the quality and quantity of human resources. The organization must always be serious about developing high-quality human resources. This research analyzes transformational work discipline, leadership style, and employee performance based on 21st century global citizens limited company. The research was held at Pratama Abadi Industri Limited Company. The method used is a quantitative survey with a sample of 70 respondents. The results of multiple regression show that the leadership style has a positive and substantial link, affecting employee performance in part. This demonstrates that the leadership style is the most important factor to consider when evaluating the performance of employees in a limited company, Pratama Abadi Industri.